Evaluation De La Durabilité Agro-Écologique Des Aménagements Hydro-Agricoles De La Plaine Inondable Dans Le Tandem Dangbo-Adjohoun Au Sud-Est Du Bénin - Mouritala Abou; Ibouraïma Yabi; Euloge Ogouwale (European Scientific Journal, ESJ, 2018)
Sustainable agriculture has become a priority in the public policies of countries like Benin, where rural people live mainly from agricultural products. However, agricultural development strategies are geared towards practices that do not meet the objectives of sustainability. This paper focuses on assessing the agro-ecological sustainability of the perimeters developed in the flood plain of Dangbo Commune and Adjohoun. In the Ouémé valley, this plain facilitates the development of a variety of hydro-agricultural developments whose agro-ecological sustainability of production conditions has been analyzed through the IDEA (Farm Durability Indicator) method. Field surveys carried out in eight 8 districts (Késsounou, Houédomey, Gbéko, Zounguè, Gangban, Kodé, Démè and Azowlissè) made it possible, using a questionnaire, to collect the qualitative and quantitative data from 254 operators of the agricultural hydro planning sites. 20 developed perimeters selected among the 66 were selected to evaluate their agro-ecological sustainability. The processing of the collected data is done according to the methods of determining the levels of sustainability. This sustainability, evaluated by thirteen indicators, thus grouping three components of the scale, yielded an average score of 58.72 out of 100. Overall, the diversity component 23.88 and the organization of space 22,79 achieved high average scores, thus contributing to the agro-ecological sustainability of the developed perimeters. On the other hand, the "agricultural practices" 12,05 constitute a component of which the lines of reflection and improvement are possible through indicators "fertilization, pesticides and protection of the ground resource" for a sustainable hydro-agricultural development.